2020
DOI: 10.1177/1357633x20932436
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ perceptions and expectations regarding digital health education and training: A qualitative study

Abstract: Introduction Digital health – the convergence of digital technologies within health and health care to enhance the efficiency of health-care delivery – is fast becoming an integral part of routine medical practice. The integration of digital health into traditional practice brings significant changes. Logic dictates that for medical practitioners to operate in this new digitally enabled environment, they require specific knowledge, skills and competencies relating to digital health. However, very few medical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Telemedicine could be incorporated into pre-existing components of the curriculum to prevent significant additional burdens for students and clinicians. 23 , 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telemedicine could be incorporated into pre-existing components of the curriculum to prevent significant additional burdens for students and clinicians. 23 , 31 …”
Section: Discussionmentioning
confidence: 99%
“… 21 Additionally, there is a noted lack of training in how to use these platforms safely and lawfully. 21 23 …”
Section: Introductionmentioning
confidence: 99%
“…In another survey study, MacNevin et al [ 35 ] showed that 79.2% of second-year medical students were “technology ready,” indicating their propensity to use new technology. However, most students do not receive formal education or training in this area [ 36 ]. Our results suggest that students are taking initiative to fill unmet needs at their respective schools, highlighting the importance of developing I&T-based education programs as part of our call for educational reform [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each clinician adopted telemedicine individually. A 2020 quantitative survey of medical students from Queensland showed that 68% (n=43) of their respondents were interested in receiving telemedicine training (40). Practically, this suggests that if telemedicine training was available to clinicians, they would be willing to receive it.…”
Section: Discussionmentioning
confidence: 99%